The Link between Cholesterol and a Brain Disease - Sujeetha Purushothaman; Arumugan Vijaya Anand (Indian Journal of Pharmacy & Drug Studies, 2023)
Lipids comprise the immensity dry mass of the brain and these have been allied with healthy function as well as the most common pathological circumstances of the brain. Genetics and lifestyles are the most important factor that influences the lipid metabolism and the key components of lipid disruption in Alzheimer’s disease (AD). Additionally, the most common genetic risk factor of AD, APOE E4 genotype, is involved in lipid transport and metabolism. Under healthy conditions, lipid homeostasis bestows a balanced cellular environment that enables the proper functioning of brain cells. However, under pathological conditions, dyshomeostasis of brain lipid can result in disturbed BBB, abnormal processing of APP, dysfunction in endocytosis/exocytose/autophagocytosis, altered myelination, disturbed signaling, unbalanced energy metabolism, and enhanced inflammation. This lipid instability may contribute to abnormalities in brain function that are the hallmark of AD. In this Review, we focus on the lipid and cholesterol metabolism, with an overview of the various lipid and cholesterol metabolic pathways and changes that have been linked to AD.